2001
DOI: 10.1556/aoecon.51.2000-2001.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in the Hungarian Economy and Foreign Trade in 1993–1998

Abstract: In this article, the authors give a rich-in-data account of Hungary's structural transition to a market economy between 1993 and 1998. Although the availability of statistics also puts constraint on which period to study, these years may as well be later termed the first phase of post-socialist transition. The article has three main parts. In the first, structural changes of the whole economy are presented; the structural shifts in output, value added, and investments are analysed. The diffusion of private own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Many studies analysed countries' (Viszt & Borsi, 2001;Huang et al, 2017;Rekiso, 2020) or sectors' (Svobodová, 2014;Sirgments et al, 2019) foreign trade balances and effects of structural changes in production. Rekiso (2020) states that, by analysing Ethiopian trade balance over one century, it was found that trade deficits are not influenced by a transition of a country, rather by the unfavourable structure of exports and majorly by economic reliance on low skill and backwardstechnology.…”
Section: Theoretical Reference To Structural Changes In Foreign Trade As a Factor Of Increasing The Competitivenessmentioning
confidence: 99%
“…Many studies analysed countries' (Viszt & Borsi, 2001;Huang et al, 2017;Rekiso, 2020) or sectors' (Svobodová, 2014;Sirgments et al, 2019) foreign trade balances and effects of structural changes in production. Rekiso (2020) states that, by analysing Ethiopian trade balance over one century, it was found that trade deficits are not influenced by a transition of a country, rather by the unfavourable structure of exports and majorly by economic reliance on low skill and backwardstechnology.…”
Section: Theoretical Reference To Structural Changes In Foreign Trade As a Factor Of Increasing The Competitivenessmentioning
confidence: 99%
“…In the following, we would like to deliver some of the findings of the research referred to in the Introduction. The investigations were carried out in the framework of an international research project (Viszt-Borsi, 1998). Although the time series corresponded to the 1993-1996 period, the findings regarding the role of FDI in foreign trade are relevant for the discussed period as well.…”
Section: The Impact Of Fdi On Hungarian Industry and Tradementioning
confidence: 99%
“…In the recent years, several in-depth studies of the Hungarian economy were completed and they often include the structural changes of industry. The most detailed analysis was elaborated in the framework of an international research project, in which a new and very interesting research methodology was used (Viszt-Borsi, 1998). The study focussed on the years between 1993 and 1996.…”
Section: Introductionmentioning
confidence: 99%